Ports in a storm : public management in a turbulent world - Donahue, John D.; Moore, Mark H., 1947- (Innovative governance in the 21st century., 2012)
In Ports in a Storm a team of Harvard Kennedy School scholars focus diverse conceptual lenses on a single high-stakes management task-enhancing port security across the United States. Their aims are two: to understand how a public manager might confront that complex undertaking, and to explore the similarities, differences, and complementarities of their alternative approaches to public management. The book takes as its pivot point the singular case of U.S. Coast Guard CaptainSuzanne Englebert and her leadership of efforts to secure America's ports after theSeptember 11 attack.